Influence of basic wood density on the specific cutting energy (Research, Society and Development, 2022)
The density of the wood influences directly on the quality of the surface, on the resistance to cutting as well as on the energy required for processing. The aim of this study was to obtain the association between specific cutting energies and basic wood densities in peripheral milling with the use of a computer numerical control. For this purpose, wood from nine species with a wide range of basic densities were used. The specimens were milled in a router with a CNC. Both the feeding and routing speeds were constant, and there was no source of variation among treatments. The values of specific energy were calculated taking into account the active power, the cutting time and the volume of wood removed. Results showed that there was a moderate correlation (r=0.61) between specific cutting energy and basic wood density data. However, by observing the particularities of each species, it was noticeable that the specific cutting energy varied as a result of factors such as the anatomical structure and the type of wood grain. It was concluded that the basic wood density has a positive correlation on the specific cutting energy required, yet it does not explain this relationship alone.